Enhanced Dielectric Loss and Magnetic Loss Properties of Copper Oxide-Nanowire-Covered Carbon Fiber Composites by Porous Nickel Film - Zeng, Jun; Zhang, Shiquan; Xue, Jun; Dai, Huili; Xia, Long; Cai, Wenyanhong; Tang, Yanhua; Xu, Chaoyi (Frontiers in Materials, 2020)
A porous nickel film of agglomerated nanoparticles, 1. 5–2.0 μm in thickness, was used to enhance the microwave absorption and ferromagnetic properties of nanowire-like copper oxide-covered carbon fiber composites. Firstly, the porous nickel film/carbon fiber composites were prepared by a plating route, using a current intensity of 120 mA for 30 min (sample S1) or 40 min (sample S2), respectively. Then, the copper oxide/porous nickel/carbon fiber composites (CNCF1 and CNCF2) were synthetized by electroless copper deposition and thermal oxidation (for sample S1 and sample S2). The microwave absorption properties of the composites were investigated over the frequency range 1–18 GHz. The results showed that the strongest reflectivity loss (RL) values of CuO/carbon fiber (CCF) and of CNCF1-2 composites were −25.93 dB at 3.59 GHz with a matching layer thickness of 2.4 mm, −27.87 dB at 6.67 GHz with a matching layer thickness of 2.5 mm, and −54.82 dB at 9.23 GHz with a matching layer thickness of 2.192 mm. When the RL values of CCF and CNCF1-2 composites were lower than −10 dB, the absorption frequency ranged from 8.12 to 9.64 GHz (1.52 GHz in absorption bandwidth, 1.5 mm in thickness), 6.45 to 8.81 GHz (2.36 GHz in absorption bandwidth, 2.4 mm in thickness), and 10.51 to 14.35 GHz (3.84 GHz in absorption bandwidth, 1.8 mm in thickness), respectively. Therefore, the CNCF2 composites showed the best microwave absorption properties and are potential microwave absorption candidates, offering thinness, strong absorption, and wide frequency.